Sustainable Management of Agricultural Research and Technology Dissemination (SMARTD) : A Strategic Framework - World Bank (World Bank, Washington, DC, 2012)
Revitalizing agriculture is critical for rural Indonesia's economic prosperity. Historically, Indonesia's dramatic poverty reduction was driven by progress in agriculture and agriculture continues to be a potent driver of growth and poverty alleviation. Agricultural sector growth strongly induces non-agricultural sector growth in rural areas, particularly through demand for locally produced and services. Agricultural sector productivity growth (along with price changes) has remained the most important way out of poverty. To shift agriculture along these dimensions, Indonesia needs to transition from its current and ineffective public stance, growing subsidies and selective output protection, to a more aggressive provision of public goods and services that build support systems for farmers to achieve continuous productivity gains. This will require an enabling agriculture policy environment, significant improvement in the delivery of services, agricultural research and extension in particular, and supporting enabling investments, which will encourage small farmers to move to high value agricultural activities. This will boost employment and raise incomes in rural areas while creating a bigger rural market with greater trade and investment opportunities.